Impact of porous complicated fin and sinusoidal-heated wall on thermogravitational convection of different nanofluids in a square domain - Sheremet, Mikhail A.; Öztop, Hakan Fehmi (Elsevier France-Editions Scientifiques Medicales Elsevier, 2021)
Porous fins due to high extended heat transfer surface are widely used in different engineering devices including heat exchangers, solar collectors, and chemical reactors. Location of these fins within the working area can be very manifold. Therefore, the present research deals with computational analysis of complicated porous fin influence on nanofluid flow and heat transfer within the heated/cooled cabinet where one vertical wall is kept at non-uniform sinusoidal temperature. The considered fin consists of the mounted porous part at the bottom adiabatic wall and inner porous zone. Investigation has been performed using the boundary-value problem for the partial differential equations formed on the basis of the conservation laws using the experimentally-based correlations for thermal properties of nanofluid. Employing the finite difference techniques the useful results have been obtained illustrating an impact of the inner porous part penetration, location of this part and nanoparticles concentration. It has been ascertained that vertical position and penetration of internal porous block can be efficacious characteristics for the heat transfer augmentation. Moreover, an addition of alumina nanoparticles suppresses the heat transfer and convective flow.
Keywords: Natural convection; Nanofluid; Porous fin; Internal porous insertion; Sinusoidal-heated border; Differentially heated region; Finite difference method